(untitled) (Prilozi za orijentalnu filologiju, 2017)
The paper deals with some of the basic features of the social history of craftsmen in Istanbul in the second half of the 18th century. The emphasis is on the social and economic conditions related to hans (hostelries). In this context, the han does not signify a place for the accommodation of travellers or lodging of single craftsmen and their ciraks, but civil facilities of various sizes where a large number of vvorkshops of the same craft were clustered. The documents at the author's disposal refer to such a han in Istanbul manufacturing and selling various kinds of fur. These are a document from the Cevdet-Iktisat Catalogue from 1168 AH (1754 AD) unpublished so far and kept in the Başbakanlik Archives, and the documents published in "İstanbul Esnaf Tarihi" 1,2 (= İstanbul Külliyatı I, VIII). In part one, general economic conditions in which the guilds operated are presented. Concentration of craftsmen of the same guild in one place had always been one of the most important characteristics of the Ottoman economic system. In the second half of the 18th century, this status in İstanbul changed considerably. The increased immigration into the city and the ownership of numerous shops by the waqf prompted dispersion of trades. One of the reasons why the craftsmen frequently abandoned their shops and looked for another location or way to provide for themselves were frequent rent rises by the waqf. Despite such tendencies of the Ottoman economic system in the second half of the 18th century, the State encouraged increasing concentration of shops of the same craft at one place. Such a system enabled easier control över trades and more efficient taxation. In addition, the concentration of craft shops at one single place sped up more successful control över production and products. Stricter societal control över such places meant, on the other hand, particular protection of their apprentices. One of the protection measures was the introduction of the icareteyn-system (double rent), as an attempt to prevent uncontrolled rent increase by the waqf. In part two, some aspects of the social life in the fur han (Valide han) from 1168 AH / 1754 AD are presented in more detail. One of the most important functions of this han was the supplying of Sultan's court with fur products. The han was to function as the central locus for the manufacture of and trade in fur in İstanbul. However, as the documents treated in our paper show, that was not the case in practice. Although the trade in fur was strictly forbidden at other places, the documents clearly prove its existence. So, we read in them that such merchants had to ran the risk of closing down their shops or even death penalties. It is interesting to mention önce more that death penalties in such cases were pronounced by kürkçü bashas. To understand better the Ottoman social, economic and cultural history, very important is the study of various aspects of guild problems in various parts of the Ottoman Empire. This paper offers a survey of the problems of the Ottoman guilds studied so far and a comprehensive insight into the existing literature.